Advokasi Kesiapsiagaan Bencana Gunung Api Berbasis Budaya dan Teknologi: Cerita Gunung Seulawah dan Gunung Fuji pada Festival Bunkasai USK 2025 - Agustina, Sylvia; Yusuf, Myna Agustina; Gani, Asri; Ardiansyah, Ardiansyah; Rusdi, Muhammad; Sofyan, Sofyan; Fakhrana, Siti Zahrina (Universitas Syiah Kuala, 2025)
This community service project focuses on disaster advocacy in Aceh, Indonesia, by drawing lessons from Japans experience with Mount Fuji. The subject of dedication is the local community and university students in Banda Aceh, particularly those with limited knowledge and preparedness regarding the volcanic hazards of Mount Seulawah. The aim of this program is to raise disaster literacy, strengthen awareness, and encourage proactive preparedness through an innovative advocacy model that combines technology and cultural approaches. The methodology of this program involved several stages: information gathering and literature review about Mount Seulawah and Mount Fuji; team discussions and planning to design advocacy content; interactive media displays such as VR application MSeulawah, 360-degree videos, banners, brochures, and cultural arts; and public advocacy conducted during the Bunkasai Festival at Syiah Kuala University. Tactics included the use of cardboard VR for immersive experiences, video screenings, interactive games to test disaster knowledge, and cultural elements such as Japanese art and traditional games to increase community engagement. The outcomes demonstrate that the integration of technology and cultural strategies was effective in attracting participation, especially among students. Visitors reported an increase in knowledge and awareness of volcanic risks, while the interactive media successfully enhanced retention and engagement. This initiative highlights the potential of hybrid advocacy models to strengthen community resilience and suggests the establishment of a Seulawah Museum as a long-term educational platform.